ENHANCING PROFESSIONAL DEVELOPMENT THROUGH APPRENTICESHIP TRAINING: A STUDY OF STUDENT OUTCOMES IN FAISALABAD, PAKISTAN - Usman Farooq; Rakhshanda Hashmi; Sabahat Gul; Sehar Anees; Rana Muhammad Amir; Hafiz Ali Raza; Dina Chamidah; Ayehsha Kanwel (International Journal of Contemporary Issues in Social Sciences, 2024)
Purpose: This study explores the impact of apprenticeship training programs on the professional development of students in Faisalabad, Pakistan. Apprenticeship training, which emphasizes learning by doing, allows students to apply their skills and abilities to real-world trade applications. The primary objectives were to examine the methods of indigenous apprenticeship induction, identify factors influencing students’ decisions to enroll, and assess the training’s effect on students’ performance. Methodology: Conducted in District Faisalabad, Punjab, Pakistan, the study involved 500 registered trainees at the apprenticeship training center. Using a 95% confidence level and a 7% confidence interval, a sample of 141 trainees was selected. Data were collected through a comprehensive, pre-tested questionnaire, and analyzed using the Statistical Package for Social Sciences (SPSS). Findings: Key findings revealed that 29.8% of respondents were aged 26-32, with the majority being government employees earning an annual income of 300,000-500,000 PKR. The most effective induction methods were practicing through trial and error and placement as assistants. Social factors such as political influence and residential background, along with educational factors like lack of professional staff and poor training quality, significantly affected the apprenticeship training. Significance: The study recommends conducting training sessions at various times to enhance trainees’ knowledge and skills, incorporating both innovative and traditional methods through collaboration with different learning centers.